Effects of Market Orientation, strategies and actions on SMEs’ Performance during fragile economic conditions - Samanta, Irene; Niros, Meletios I.; Pollalis, Yannis A. (Archives of Business Research, 2020)
Purpose –The purpose of this research is to unveil effective SME marketing actions and strategies in terms of performance during post-crisis era of fragile economic conditions. This paper further examines the effects of IT Marketing Infrastructure (ITMI) on both performance and Customer Equity Drivers (CEDs). Last, but not least, indirect effects of Market Orientation (MO) on Performance are also researched. Design/methodology/approach – A personal interview survey was conducted in Greece using a structured instrument deriving from adjusted items of past research. A systematic random sample of 242 SMEs was collected from major Greek cities and a wide range of industries. Findings – Findings unveiled that the same actions applied by large companies, also work for SMEs/VSEs. In addition, ITMI enable smaller firms to apply marketing strategies required to achieve higher Marketing Performance. However, MO is the key for excessive performance. Nevertheless, the indirect effect of MO on the relationship between marketing strategy and OP is negative, illustrating a need of strategic focus for SME. Research limitations/implications – Despite survey presents certain trends and inference, it lacks qualitative data such as sentiments that are of equal importance in SME research. Practical implications – This research facilitates SMEs to decide on effective actions against fragile economic conditions to achieve higher performance. In addition, it demonstrates the need to bolster chain value through ITMI. In specific, ITMIs forge core capabilities to apply CEDs that result in greater MO and Performance. Moreover, MO is proven to be a key factor to sustain higher levels of Performance when applying either a RE or a VE strategy. Originality/value – In spite of the existence of research of effective actions and strategies during recessions, there is lack of SMEs research regarding fragile economic conditions after recessions or crises. ITMI and MO will facilitate SMEs to apply CEDs and sustain higher Organizational Performance.